Learning Strategies at SMP Muhammadiyah 5 Reinforcement to Increase Student Interest in Distance Learning - Aulia Risa Eksanti (Proceedings of The ICECRS, 2021)
This study aims to determine the strategies adopted by SMP Muhammadiyah 5 Tulangan to increase students' interest in learning in distance learning. As a result of the Covid-19 pandemic, all schools implement a distance learning system with an online system. This is in accordance with PERMENDIKBUD NUMBER 15 OF 2020 concerning Guidelines for Organizing Learning From Home in an Emergency Period for the Spread of Corona Virus Disease (COVID-19). So that SMP Muhammadiyah 5 Tulangan also implements a distance learning system. In collecting data, I used a qualitative research method by interviewing one of the teachers of SMP Muhammadiyah 5 Tulangan. With the results of students at SMP Muhammadiyah 5 Tulangan experiencing a decrease in interest in learning during distance learning due to boredom or boredom with the distance learning system. The strategies adopted by SMP Muhammadiyah 5 Tulangan in increasing students' interest in learning during distance learning include using more varied learning methods and will be explained in more detail in the discussion.